Sheep and goat feeding behavior profile in grazing systems - Dias e Silva, Tairon Pannunzio; Abdalla Filho, Adibe Luiz (Acta Scientiarum. Animal Sciences, 2020)
Feeding behavior analysis provides information about the relationships between animals and pastures. Therefore, this review aims to describe some aspects of the feeding behavior profiles of both sheep and goats in grazing systems. The structure of the pasture is a key factor in the feeding behavior of grazing animals. The amount of feed consumed in a given period of time is affected by the number of meals, duration and velocity of swallowing, changes in grazing time, bite rate, bite weight, and quality of ingested forage. The different phenological stages of forage also influence the animals’ strategies to optimize their intake, which consequently changes their behavioral activities. Sheep and goats tend to be more selective than cattle, and young animals are more selective than older animals; this selectivity characteristic is one of the most important aspects to be observed in pasture management. According to the degree of selectivity, the animals will intake forages of higher or lower nutritive quality. In addition, the intensity and distribution of their daily activities (grazing, ruminating, and resting) are influenced by several factors, such as the availability and nutritive value of the pasture, its management, the animal activity in the group, and the predominant climatic conditions of the region.